Islamic Educational Games to Increases Students' Understanding and Interest in Studying Asmaul Husna in SD S Tahfidzul Quran Raudhatul Hasanah - Hastuti, Ari Widia (Jurnal Profesi Guru Indonesia, 2024)
A study entitled "The Application of Islamic Educational Games Increases Students' Understanding and Interest in Learning About Asmaul Husna in SDS Tahfidzul Quran Raudhatul Hasanah" has been conducted. The purpose of this research is to find out students' understanding, students' interest in learning and students' response to the application of the Islamic educational game kartu asmaul husna. This type of research is Class Action Research (PTK) which is done in two cycles. Implementation time January-March 2025. The subject of the research is class IV students at SDS Tahfidzul Quran Raudhatul Hasanah as many as 25 people consisting of 11 male and 14 female students, as well as 5 teachers. Research instruments include comprehension test questions, observations, teacher interviews, and student learning interest questionnaires. Data analysis is done with a percentage formula. Based on data analysis, the average percentage of student activity at meeting I was 65.13% (sufficient category) and at meeting II the activity was 84.72% (very good). The average learning result obtained is 90, 24 of which are included in the very good category. Student response to the application of katu asmaul husna game in giving an agreeable response of 75.41% compared to a skeptical response of 18.72%.